Genetic Parameters Character Yield of Component 20 Selected Genotypes F4 Soybean (Glycine max L.) Pedigree Selection - Sihaloho, Arvita Netti; Galingging, Irawaty Rosalyne; Sitinjak, Wahyunita; Simarmata, Marulam MT; Purba, Tioner (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
A character with a good genetic parameter can be used as a selection character. The study aims to identify a genotype with high production. The research was done in augmented, which is the methodology that does not use repetition for the F4 generation but involves repetition for both parents. All plants were planted on a plot. Twenty seeds of the F4 genotype (planted as 40 plants for every genotype), Argomulyo, and Tanggamus were planted as 60 plants with 3 times repeated. Character components of yield examined are the number of branches per plant, the number of pods per plant, seed weight per plant, and the weight of 100 seeds. The calculations were conducted to estimate heritability, the genetic variability coefficient (GVC), as well as skewness, kurtosis, and correlation. The results obtained genotypes that have the opportunity to produce high yields are F4.5.82.87.104 = G7 because the action of genes that play a role, are complementary epistasis, additive, and the number of genes is small, and the value of a large correlation, real positive between the number of branches with the number of pods per plant.